Evaluation of the Effectiveness of the Kaltim Tuntas Scholarship Program in Samarinda - Kresnina; Daryono Daryono; Anwar Alaydrus (Poltanesa, 2025)
This study evaluates the implementation of the “Kalimantan Timur Tuntas” Scholarship Program in Samarinda using William Dunn’s program evaluation framework, which includes six key criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The research applies a qualitative descriptive approach by collecting data through interviews with stakeholders, direct observations, and analysis of relevant secondary documents. The scholarship program, launched in 2019 and managed by the East Borneo Scholarship Management Agency, aims to provide equitable access to higher education and foster the development of competitive human resources in anticipation of the region’s strategic role as the location of Indonesia's future capital, Nusantara. Findings indicate that the program has made significant progress in expanding educational opportunities, particularly for marginalized groups. However, several systemic challenges persist, including uneven distribution of benefits favoring urban areas, limited adaptability to economic fluctuations (such as inflation), and inadequate mechanisms for real-time feedback and program adjustment. Moreover, discrepancies in administrative execution and gaps in digital infrastructure have hindered accessibility for students in remote and underdeveloped regions. The study underscores the need for more inclusive and adaptive policy designs that account for regional disparities. Recommendations include adopting a dynamic and needs-based allocation model, enhancing inter-agency data integration, increasing transparency in the selection process, and establishing a participatory monitoring and evaluation system. The study concludes that while the program contributes to educational equity in Kalimantan Timur, further improvements are necessary to ensure long-term effectiveness and sustainability in achieving the broader goal of social mobility and human capital development.